Prognosis: The Plan of Integrated Tourism Area of Kapuk Naga Beach, Tangerang, West Java - Priyono, Kuswaji Dwi (Forum Geografi, 1997)
This paperÂ tries to analyze of prognosis of the Integrated Tourism Area Planning of Kapuknnaga Beach (KWTPK) Tangerang Regency West Java. The two method applied to compose the prognosis are extrapolation and indication. The extrapolation is based on the local area infomation data of contemporary knowledge in the past and presence, while the indication method utilizes the whole interrelation activities programmed with the possible consequences. Land function transformation effects of KWTPK will cause environmental destroy as annual flsh flood, salt water intrusion and polution of urbanâs industry sewage. As further effect there is a raising of turbidity and nitrition degree of sedimentation which make coral-ridge degradation toward annihilation. The coral-ridge annihilation will cause the sea waves power collide with the seashore area directly which threatens KWTPK.